Neurobiological modulation with REAC technology: enhancing pain, depression, anxiety, stress, and quality of life in post-polio syndrome subjects - André Nogueira, Jeyce Adrielly; Souza Bulle Oliveira, Acary; Pereira Motta, Monalisa; Vieira de Souza Moscardi, Alcione Aparecida; Manchim Favaro, Vanessa; Munhoz Teixeira, Claudete; Orasmo Simcsik, Amanda; Patrizi, Maria Clara; Conde, Maria Salete; Rinaldi, Arianna; Fontani, Vania; Rinaldi, Salvatore (Scientific reports, 2024)
Post-polio syndrome (PPS) brings new challenges for polio survivors, including muscle decline, pain, depression, and diminished quality of life. This study explored the potential of REAC neuromodulatory treatments to ease pain, improve mood, and enhance quality of life in PPS patients. 17 individuals with PPS (average age 54.8) received three REAC treatments: Neuro Postural Optimization, Neuro Psycho Physical Optimization, and Neuro Psycho Physical Optimization-Cervico Brachial. Pain, depression, anxiety, stress, and quality of life were assessed before and after using established scales. REAC treatments significantly reduced pain across various dimensions, along with depression, anxiety, and stress levels. Additionally, patients reported improved physical and psychological quality of life. This study suggests REAC neuromodulatory treatments as a promising non-invasive option to improve pain, emotional well-being, and quality of life in individuals with PPS.